Macular and Retinal Nerve Fiber Layer Thickness Changes in Adolescent Patients after Cataract Surgery - Mir Alam Siddique; Arup Jyoti Dev Sarma; Kamal Hasan; Nasima Sultana; Sultana Jesmin Ahmed (Delhi Journal of Ophthalmology)
Purpose: This study analyzed macular thickness (FMT) and retinal nerve fiber layer thickness (RNFL) following phaco-aspiration (PHACO) and small incision cataract surgery (SICS) in adolescent eyes. Methods: Macular thickness and RNFL thickness were measured using optical coherence tomography (OCT) in 52 eyes who underwent PHACO or SICS surgery. OCT measurements were done preoperatively, and on 1st, 14th, 42nd, 84th and 168th postoperative days. Eyes with any other diseases were excluded. Paired sample t-test was used to compare the parameters. Results: The FMT and RNFL thicknesses were found to be higher postoperatively. The SICS group had significantly higher macular thickness (233.06 ± 31.23 µm) than the PHACO group (227.33 ± 28.25 µm) on the 42nd day. The RNFL thickness in SICS was significantly higher than in PHACO and highest on the 84th postoperative day, with mean average value 95.04 ± 16.61 µm and 91.98 ± 18.22 µm respectively. Conclusions: This study shows that cataract surgery increases the macular and RNFL thickness. These increases are significantly higher in the SICS than in PHACO eyes on the 42nd day after surgery, which resolves gradually towards 168th day after surgery. This indicates that phaco aspiration is more preferable surgery then SICS in adolescents with regard to postoperative increase in macular and RNFL thickness.